ANALISIS IDENTITAS VISUAL “YK” SEBAGAI BAGIAN DARI CITY BRANDING KOTA YOGYAKARTA - Davina Naja Suryantoro; Naomi Haswanto (Wimba : Jurnal Komunikasi Visual, 2025)
City branding is an effort to form a brand of a city with the aim of introducing and marketing the city to the target. As a city that is famous for its natural and cultural tourism, city branding is very important for the City of Yogyakarta to develop its region. This study uses qualitative methods with descriptive data analysis. The theories used are the theory of visual identity and city branding hexagon, which are used to analyze YK's visual identity, then analyze it again in terms of the variables in city branding hexagon. The results of the analysis that has been carried out show that the YK logo conveys the City of Yogyakarta's efforts to compete in the globalization era by giving a modern impression through the selected composition and typography that is different from Jogja Istimewa, but this makes YK's position unclear as a part of Jogja Istimewa. Through the city branding hexagon, it can be seen that the use of YK’s branding by the public is still minimal and it does not look optimal in several aspects due to its still short lifespan. This research is expected to be a reference for further research in building the city branding of the city of Yogyakarta.